Severe Constipation in Parkinson's Disease and in Parkinsonisms: Prevalence and Affecting Factors - Frazzitta, Giuseppe; Ferrazzoli, Davide; Folini, Annarita; Palamara, Grazia; Maestri, Roberto (Frontiers in Neurology, 2019)
Background: constipation is one of the most common and disabling non-motor symptoms of Parkinson Disease (PD) and Parkinsonisms (PS). Few studies evaluate the difference of prevalence between PD and PS and the cause leading to a severe constipation in this diseases. Objective: Aim of our study is to evaluate the prevalence of constipation in a population of patients with PD and PS and to evaluate which factors influence the development of severe constipation. Methods: 250 outpatients with PD and 39 with PS were enrolled. 65 age-matched healthy subjects served as control. Constipation was assessed using the “Constipation Scoring System” (CSS). All patients underwent a global clinical, functional and neuropsychological assessment including: UPDRS, Six-minute Walk Test (6MWT) and MMSE. Results: data confirm the high prevalence of constipation among patients with PD and PS. Severe constipation affects much more patients with PS. A significant association between total CSS and age, H&Y stage, 6MWT, MMSE, total UPDRS and UPDRS III was found in PD. In PS patients total CSS was associated with age, 6MWT, total UPDRS and UPDRS III. Multivariable regression analysis showed that the only variables significantly and independently associated with total CSS in PD patients were age and total UPDRS, both with direct relationship. Conclusions: The reduction of motor performance seems to be the primary cause for developing severe constipation in PD and PS patients. These data suggest that maintain a good quality of gait and endurance may be helpful to reduce the risk of constipation.